La legítima defensa y el uso excesivo de la fuerza como desventajas jurídicas a la seguridad ciudadana. - Narvaez Naranjo, Cesar Rene (2015)
This research work aims to demonstrate that from the publication and validity of the new constitution the same that was approved and promulgated as of October 20, 2008, brings a new range of actions that lead to demonstrate the importance of the National Police, society in general and the decision that a new paradigm is emerging with the flowering of public policies implemented with good living, so m, the present work, it is necessary as a proposal is made cash said statement by the Constitution and society.